Anti‐Aggregation of Nanosized CoS2 for Stable K‐Ion Storage: Insights into Aggregation‐Induced Electrode Failures. Issue 29 (7th June 2022) - Zhang, Hehe; Cheng, Yong; Sun, Jingjie; Ye, Weibin; Ke, Chengzhi; Cai, Mengting; Gao, Haowen; Wei, Ping; Zhang, Qiaobao; Wang, Ming‐Sheng
Abstract: As promising conversion‐type anode materials for potassium‐ion storage, transition metal chalcogenides (TMCs) exhibit high energy density but suffer severe capacity fading, which is generally ascribed to their large volume expansion and the associated structural degradation. Instead, this study emphasizes that the aggregation of nanosized TMCs during conversion reaction is a more crucial reason for the following serious electrode failures. This issue has not received enough attention, and especially the detailed aggregation mechanism and its relationship to electrode failures remains unclear. Thus, by combining in situ and ex‐situ electron microscopies, the aggregation evolution of nanosized CoS2 is systematically investigated from micro to macro scale. The aggregation originates from the coalescence of the K2 S matrix during potassiation, which constantly develops into larger‐scale agglomerates as the cycling continues, eventually leading to electrode fragmentation, etc. To address this issue, an anti‐aggregation strategy is proposed through isolating CoS2 nanoparticles inside individual carbon nanoshells. Impressively, the CoS2 aggregation is strictly confined within each nanoshell, which prevents their extensive aggregation across the electrode, resulting in the superior structural and electrochemical stability. This work reveals the mechanism of aggregation‐induced electrode failures and proposes the necessity of anti‐aggregation of nanosized active materials for the design of high‐capacity electrodes. Abstract : By cross‐scale observation of the structural evolution of nanosized CoS2 upon potassiation, the mechanism of CoS2 aggregation is revealed, which is found to be a crucial reason for the following serious electrode failures. An anti‐aggregation strategy is further proposed through isolating CoS2 nanoparticles inside individual carbon nanoshells, which prevents their extensive aggregation across the electrode, resulting in superior electrochemical stability.